Học phần tăng cường tiếng Anh cấp độ B1: Reading - Lê Thị Phương Lan (Trường Đại học Thuỷ Lợi, 2020)
It contains 12 units. Each unit focuses on a different topic and these topics are ones that often appear in IELTS exam